2021
DOI: 10.1088/1361-6668/ac1523
|View full text |Cite
|
Sign up to set email alerts
|

In-situ measurements of the effect of radiation damage on the superconducting properties of coated conductors

Abstract: An apparatus has been built to perform irradiation and electrical testing of REBCO coated conductors (CC) held below their critical temperature (T c ). Patterned tracks of Fujikura GdBCO CC were irradiated with 2 MeV He + ions in steps up to 4 mdpa whilst held at 40 K, and the critical current density (J c ) determined from I-V characteristics. These 'in-situ' samples then underwent annealing experiments at room temperature. The superconducting performance, both before and after room temperature annealing, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Considering the intended use of REBCO-coated conductors in thermonuclear fusion reactors, the robustness against fast neutron irradiation is a crucial issue that needs to be addressed [4,[16][17][18]. Because experiments with fast neutron irradiation are slow and expensive and create radioactive samples, these studies are complemented with studies that use Helium ion irradiation as a proxy [19]. This raises the question of the extent to which the irradiation damage created by fast neutrons and helium ions is comparable.…”
Section: Technol 36 10lt01)mentioning
confidence: 99%
“…Considering the intended use of REBCO-coated conductors in thermonuclear fusion reactors, the robustness against fast neutron irradiation is a crucial issue that needs to be addressed [4,[16][17][18]. Because experiments with fast neutron irradiation are slow and expensive and create radioactive samples, these studies are complemented with studies that use Helium ion irradiation as a proxy [19]. This raises the question of the extent to which the irradiation damage created by fast neutrons and helium ions is comparable.…”
Section: Technol 36 10lt01)mentioning
confidence: 99%
“…Iliffe et al reported that the T c of a GdBCO CC irradiated with He + ions at cryogenic temperatures (40 K) degraded significantly stronger at a comparable calculated number of displacements per atom (dpa) than the SP SCS4050-2013 tape in this study. Heating up the sample to room temperature led to a recovery in T c of ∼10 K [15]. Taking into account the results from Fischer et al annealing begins at 120 K, leading to a much steeper recovery slope of approximately 5.8 K/100 • C [16].…”
Section: Recovery Of the Critical Temperaturementioning
confidence: 99%
“…Recent in-situ experiments showed that He + irradiation at cryogenic temperatures led to faster degradation of the superconducting critical current density j c and the critical temperature T c than irradiation at room temperature. Warming up the samples to room temperature led to partial recovery of the observed additional degradation starting from temperatures of only 120 K [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great improvements in magnet technology and reactor design that have recently been achieved, several challenges still need to be faced in order to deliver fusion reactors, one of the greatest being the evaluation and optimization of radiation hardness of the involved materials, including HTSs [3].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, all the research carried out on the radiation hardness of HTS tapes is either performed with fission neutrons [7][8][9][10][11][12][13] or with ion irradiation [3,14], yielding extremely valuable but unavoidably incomplete information. We suggest that a full understanding of radiation damage in HTS tapes can be achieved through the comprehensive analysis of several experimental approaches, each shedding light on specific issues, combined with a thorough computational investigation of the expected damage under working conditions.…”
Section: Introductionmentioning
confidence: 99%